PHARMACOGNOSY OF AZIMA TETRACANTHA LAM.: A REVIEW - Nandhini, *Sundaresan; Radha, Ramalingam (International Journal of Ayurveda and Pharma Research, 2016)
Plants have played a central role in the prevention and treatment of diseases since prehistoric times. In recent years, there has been growing interest in the study of medicinal plants and their extensive use in different countries. However, today it is essential to pay for the scientific proof as to whether it is rational to use a plant or its active principles. Hence the present communication constitutes a review with adequate information on the medicinal properties, ethno medicinal uses, phytochemistry, and pharmacological activities of an Indian medicinal plant, Azima tetracantha Lam belonging to the family of Salvadoraceae. A wide range of phytochemical constituents have been isolated from A. tetracantha Lam which possesses activities like as stimulant, expectorant, antispasmodic, analgesic, anti-inflammatory, anti-ulcer, anti-diarrhoeal, anti-microbial, hepatoprotective, nephroprotective, hypoglycemic and hyperlipidemic activities. Hence, extracts of Azima tetracantha could form one of the best options for developing novel natural medicine.